Effects of tissue and gender on macromolecule suppressed gamma‐aminobutyric acid. Issue 2 (June 2017) - Saleh, Muhammad G.; Near, Jamie; Alhamud, Alqadafi; van der Kouwe, André J. W.; Meintjes, Ernesta M.
Abstract: The aims of this study are to determine the ratio of concentration of GABA in grey matter to concentration of GABA in white matter (GABAGM /GABAWM ) and compare with literature values, and to investigate gender‐related differences in GABA in healthy subjects. Twenty healthy subjects were scanned using a motion and shim navigated MEGA‐SPECIAL MRS sequence. For every subject, two acquisitions were performed for each of two regions, the anterior cingulate cortex (ACC) and medial‐parietal cortex (PAR), with the order interleaved. Absolute GABA (GABAH2O ) and GABA/Cr concentrations were measured using LCModel. LCModel fitting revealed an overall average Cramer–Rao Lower Bounds ≈10%. The GABAGM /GABAWM for both GABAH2O and GABA/Cr are 3 and 1.5, respectively, and in agreement with the literature. The ACC revealed no gender‐related differences in GABA. The PAR revealed time‐related changes in concentrations of GABA in male participants and thus gender‐related differences. The higher concentration of GABA in GM than in WM found in this study and literature might be reflective of heterogeneous distribution of GABA around the brain. The gender‐ and time‐related differences in the PAR emphasize that gender‐ and time‐matching are critical for GABA scans.